ANALISIS KEBIJAKAN AKUNTANSI ATAS PERLAKUAN ZAKAT AKTIVA PADA PT. BANK BNI SYARIAH CABANG MAKASSAR - Khaliq, Abdul (Universitas Muhammadiyah Makassar, 2020)
Accounting Policy Analysis of Zakat Asset Treatment at PT. Bank BNI Syariah Makassar Branch. This research aims to determine the accounting policy for the zakah treatment of assets in PT.Bank BNI Syariah Makassar Branch and the influence of zakat on sharia accounting policies. The method of analysis used is descriptive qualitative analysis method by using data collection technique that is observation and interview. From the results of research conducted at PT.Bank BNI Syariah Branch of Makassar on accounting policy for the zakah treatment of assets. Where in the accounting policies that exist in PT. Bank BNI Syariah Branch of Makassar level of quality of information provided to the public, where the zakat management agency should be able to convince the public that BNI Syariah Bank Makassar Branch has the ability and capacity in achieving program objectives in accordance with Islamic Shari'a in the management of zakat that requires the resources human beings who have managerial skills, religious knowledge, sufficient technical skills.